2021
DOI: 10.3390/cells10102593
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Intestinal Permeability in Irritable Bowel Syndrome-Like Disorders: Histological and Ultrastructural Findings of Duodenal Biopsies

Abstract: Background and Aim: Diarrhea, abdominal pain, and bloating are frequent in irritable bowel syndrome (IBS)-like disorders, although little is known about their intestinal ultrastructural alterations. The aim of the present study was to study duodenal biopsies from IBS-like patients to find ultrastructural alterations. Materials and Methods: Study design: descriptive comparative pilot study. Thirty outpatients (9 male and 21 female; median age 37.7 years; range, 20 to 65 years) complaining of IBS-like symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…Intestinal epithelial barrier dysfunction and increased permeability have been described in disorders of the gut brain axis [1,2,3]. A tight junction barrier defect that enhances disease progression has been suggested in postinfectious IBS and FD [11,14,15,16,17,20]. In a recent paper, Noikow et al [14] reported duodenal mucosal probe based confocal laser endomicroscopy (pCLE) abnormalities in patients with FD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal epithelial barrier dysfunction and increased permeability have been described in disorders of the gut brain axis [1,2,3]. A tight junction barrier defect that enhances disease progression has been suggested in postinfectious IBS and FD [11,14,15,16,17,20]. In a recent paper, Noikow et al [14] reported duodenal mucosal probe based confocal laser endomicroscopy (pCLE) abnormalities in patients with FD.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that low-grade inflammation exists in the duodenum of patients with FD and IBS [4,5,6,7,8,9,10,11]. The intestinal hyperpermeability may enable noxious microorganisms, their toxins and antigens to "leak" into the duodenal wall and bloodstream and consequently trigger reactions in both gastrointestinal and non-gastrointestinal diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время нарушение функции мукозального барьера и повышение кишечной проницаемости считается одним из основных патогенетических механизмов развития СРК [27]. Известно, что проникновение антигенов из просвета кишечника во внутреннюю среду организма может способствовать чрезмерной антигенной стимуляции и формированию воспаления низкой степени активности в слизистой оболочке кишечника, характерного для СРК.…”
Section: мукозальный барьер как основа поддержания гомеостазаunclassified
“…[3][4][5] Additionally, increasing evidence suggests enhanced intestinal permeability, dysregulated microbiome and changes in immune function contribute to IBS. [6][7][8] Intestinal mucosa damage and dysbiosis of the intestinal microflora lead to the permeation of harmful substances such as pathogenic bacteria or antigens into the bloodstream or other organs, contributing to the development or exacerbation of multiple organ dysfunction and inflammation. 9,10 While immunomodulators and antibiotics are commonly used to alleviate symptoms, their adverse side effects and high rates of drug resistance impact patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the symptoms of IBS involve dysfunction of interactions between central and peripheral nervous system factors, low‐grade inflammation, and intestinal infections 3–5 . Additionally, increasing evidence suggests enhanced intestinal permeability, dysregulated microbiome and changes in immune function contribute to IBS 6–8 . Intestinal mucosa damage and dysbiosis of the intestinal microflora lead to the permeation of harmful substances such as pathogenic bacteria or antigens into the bloodstream or other organs, contributing to the development or exacerbation of multiple organ dysfunction and inflammation 9,10 .…”
Section: Introductionmentioning
confidence: 99%